Changes in testicular tissue in obstructive azoospermia with an increase in the duration of the disease - Lesovoy, V. N.; Panasovskiy, N. L.; Tovazhnyanska, V. D. (Journal of Education, Health and Sport, 2020)
To understand the infertility development it is important to study how individual components of the connective complexes of Sertoli’s cells are formed and developed in order to allow not only individual cells, but also entire syncytia of germ cells to migrate from the basal to the adluminal compartment of the spermatic epithelium, without causing loss of permeability. Testicular tissue changes in azoospermia with an increase in the duration of the disease and the prognosis of the possibility of conception are of particular interest. The aim. To reveal changes in the testicular tissue on azoospermia with an increase in the duration of the disease. Materials and methods: to achieve the aim, a pathomorphological study was carried out. The material for the study was testicular biopsies of patients aged 26-45 years with a diagnosis of obstructive azoospermia (OA). The material was divided into three groups: group 1, control: healthy fertile men; group 2 (study group): men of mature age (26–45 y. o.) with a clinical diagnosis of OA up to 5 years of duration. Group 3 (study group): men of mature age (30–45 y. o.) with a clinical diagnosis of OA up to 10 years of duration. The preparations were studied macroscopically, microscopically, morphometrically and immunohistochemically. Results and discussion. Healthy spermatogenesis was typical for all control group samples. In group 2 (disease up to 5 years from the previous conception) there were three spermatogenesis samples out of eight. There were focal processes of fibrosis and hyalinosis, with focal proliferation of interstitial tissue. In the the group of men with OA lasting up to ten years from the previous conception, the absence of healthy spermatogenesis in all cases was noted. Conclusions.1. In the group of men with OA lasting up to five years from the previous conception there were violations of spermatogenesis, a decrease in the transport of biologically active substances through the blood-testicular barrier. The latter leads to degenerative processes in the germ cells.2. In the group of men with OA lasting up to ten years from the previous conception, there was a pronounced deterioration in spermatogenesis, the transition of OA to NOA with increased duration of the pathological process. The latter significantly worsens the prognosis of the disease course and significantly reduces the possibility of conception.